Projection of Indonesian Islamic commercial banks efficiency and stability in the Covid-19 period using DEA and panel ARDL - M. Fikri Himmawan; Novian Abdi Firdausi (Jurnal Ekonomi & Keuangan Islam, 2021)
Purpose – This study aims to assess the efficiency and stability of Indonesia Islamic Commercial Banks, and then the results are used as a projection in the Covid-19 period. It uses the sample from 14 Islamic Commercial Banks in Indonesia and its quarterly data from 2017 to 2020.Methodology – The DEA method analyses VRS and CRS scale using output orientation. The Panel ARDL also uses two models from the specifications in DEA, with the inputs as independent variables and the outputs as dependent variables.Findings – The result of DEA is visualized in four quadrants from each CRS and VRS model. Respectively in each model, 1 and 5 banks are highly efficient and stable, 5 and 2 banks have high efficiency but low stability, 4 and 2 banks have low efficiency but high stability, 4 and 5 banks have low efficiency and stability. In the Panel ARDL, third party fund, operational expenses, and total financing have significant and stable long-run effect in both models. In the short-run, only operational expenses significantly affect operational earnings, whereas only total financing significantly affects total assets.Practical implications – Banks may use strategies such as absorbing workforces as marketing representatives, utilizing cooperative agreements, crowdfunding, improving banking technology, creating provisions on expected credit loss, and deferring profit.Research limitations – The limitation of this study is the small sample size because only 14 Islamic commercial banks are used as the sample, without considering the Islamic business units of the conventional banks so the predictive strength of the result only constrained in the Islamic commercial banks.Originality – The study uses two different methods in assessing Islamic Commercial Banks especially in the Covid-19 period, hence adding insights on Islamic Commercial Banks in the pandemic period and further contributes to the Islamic banking field of study.